Representações de professores de língua inglesa para crianças sobre a avaliação da aprendizagem na perspectiva sociointeracionista - Pacianello, Katiana (2023)
The present research, of a qualitative-interpretative nature (DENZIN; LINCOLN, 2007), has the main objective of investigating the English teachers‟ representations about assessment in English language for children. The relevance of this subject is related to the reflective didactic approach that contributes to reflective actions in relation to educational assessment in English Language for Children (ELC) as a constant part of the teaching-learning process. The research involved the participation of English teachers of Early Childhood Education and Elementary School -initial years- from the Municipal Department of Education of the city of Francisco Beltrão, in the southwest region of Paraná, who participated in the Teacher Outreach Course in English Language for Children, offered by the Portuguese-English Language Teaching Course of the Federal Technological University of Paraná, in 2022 and the first semester of 2023. Given this authentic context, data generation was done through remote (synchronous) and in-person meetings that constituted one of the modules of the course, entitled “Learning Assessment”, whose workload corresponded to twelve hours, aiming at the continued education of these professionals. At the meetings, concepts and methodologies were worked on, regarding the assessment of learning in English for children aged 3 to 5 years old (early childhood education) and aged 6 to 10 years old (Elementary Education). The meetings were audio-recorded and then transcribed, based on Pretti (1999), for data analysis. Furthermore, a questionnaire on the topic was implemented in the first meeting, as a way of understanding the participants' representations before the researcher's intervention. Data analysis refers to content analysis (BRONCKART, 2006, 2012) and is based on studies about the learning assessment in general, and, specifically on English language learning from a socio-interactionist perspective (VYGOTSKY, 1989, CAMERON, 2001, LUCKESI, 2001, DUBOC, 2007, 2015; BALBINO, 2022; BALBINO, TONELLI, 2021; FURTOSO, 2011; TONELLI; QUEVEDO-CAMARGO, 2019, among other studies of the area). As a result, we obtained representations that: a) carry strong reverberations from traditional assessment theories, but which teachers have been trying to deconstruct because they understand that assessment requires an environment favorable to teaching; b) there is a need to promote literacy in ELC assessment for teachers for the benefit of students; and c) these participant teachers have been on continuous teacher education on their own teaching practices, still on the way of understanding their role, so important to their students.